Використання моделювання при навчанні учнів професійно-технічних навчальних закладів робітничим професіям - Шматков, Е. В.; Шматков, Д. І. (НТУ "ХПІ", 2009)
Possibility of the model going is rotined near mastering student Ptuzov of separate receptions and labour operations of workings professions of metal-working type. Examples are resulted, how this approach can be used for a capture an integral working profession "machine-operator of wide type"
Keywords: освітнє середовище; внутрішньовузівська система освіти; верстатник широкого профілю; виробниче навчання; модельний підхід